A new puppet puzzle. (1st September 2020) - Bailey, Andrew M.; Rasmussen, Joshua
Abstract : We develop a new puzzle concerning a material being's relationship to the smallest parts of the material world. In particular, we investigate how a being could be responsible for anything if its behavior is completely determined by the behavior of those small parts. Many discussions of determinism and responsibility have focused on a determinism that moves from past to future. The determination at issue in our paper is importantly different: it moves from the bottom up.